2015
DOI: 10.1371/journal.pone.0118522
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and Contemporary DNA Reveal a Pre-Human Decline but No Population Bottleneck Associated with Recent Human Persecution in the Kea (Nestor notabilis)

Abstract: The impact of population bottlenecks is an important factor to consider when assessing species survival. Population declines can considerably limit the evolutionary potential of species and make them more susceptible to stochastic events. New Zealand has a well documented history of decline of endemic avifauna related to human colonization. Here, we investigate the genetic effects of a recent population decline in the endangered kea (Nestor notabilis). Kea have undergone a long-lasting persecution between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 119 publications
0
30
0
Order By: Relevance
“…One analysis grouping individuals per geographic origin (South, Central and North; see results), and a second analysis with all individuals grouped together. Two mutation models were chosen, the TPM model for microsatellites (Di Rienzo et al 1994) with 90% and 95% stepwise mutations following Garza and Williamson (2001) and Dussex et al (2015) with a variance of 12 as suggested by Piry et al (1999), to encompass the observed range of multistep mutations in natural populations (Di Rienzo et al 1994); and the stepwise mutation model (SMM). The mode-shift test was used as implemented in Bottleneck v1.2.02 to assist in discriminating between recent bottlenecked and stable populations .…”
Section: Demographic Historymentioning
confidence: 99%
See 2 more Smart Citations
“…One analysis grouping individuals per geographic origin (South, Central and North; see results), and a second analysis with all individuals grouped together. Two mutation models were chosen, the TPM model for microsatellites (Di Rienzo et al 1994) with 90% and 95% stepwise mutations following Garza and Williamson (2001) and Dussex et al (2015) with a variance of 12 as suggested by Piry et al (1999), to encompass the observed range of multistep mutations in natural populations (Di Rienzo et al 1994); and the stepwise mutation model (SMM). The mode-shift test was used as implemented in Bottleneck v1.2.02 to assist in discriminating between recent bottlenecked and stable populations .…”
Section: Demographic Historymentioning
confidence: 99%
“…Examining spatial patterns of genetic diversity is an important component of conservation planning and implementation (McNeely et al 1990, DeSalle and Amato 2004, Arif and Khan 2009. Interpreting the processes underlying spatial patterns observed in genetic data is difficult, as the genetic diversity present in a population is a product of both long-term processes, such as global climate change, as well as more recent anthropogenic factors such as habitat loss, pollution, introduced species, disease, poaching and over-exploitation of natural resources (Bouzat et al 1998, Bickham et al 2000, Daszak et al 2000, Bouzat 2010, Dussex et al 2015. Both long-term and more recent human-associated factors can fragment habitat and reduce population size which can lead to populations with lowered genetic variation, evolutionary potential and mean population fitness (Shaffer 1981, Couvet 2002, Spielman et al 2004, Bruggeman et al 2010, dos Anjos et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the same 48 microsatellite loci screened for variability, genetic diversity is ~48% less within Hawaiian gallinule (1.44 alleles/locus, 1–3 alleles observed, 31 loci monomorphic) than Hawaiian coot (2.75 alleles/locus, 1–7 alleles observed, 15 monomorphic, based on 10 individuals; Sonsthagen et al., ; SAS unpublished data). Ancient reductions in genetic diversity have been postulated to limit the signature of recent population declines (e.g., Dussex et al., ; Taylor & Jamieson, ). Given that genetic diversity was likely already low prior to decline for Hawaiian gallinule, the observation of genetic structuring between sample time periods is even more noteworthy because genetic drift had little variation on which to act indicating that the individuals that survived the bottleneck had a strong influence on the evolutionary trajectory of the Oahu population.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-lived species can reduce the effective time spent experiencing a bottleneck thus enabling the retention of genetic diversity over short timescales (e.g., Hailer et al, 2006;Johnson, Gilbert, Virani, Asim, & Mindell, 2008;White et al, 2014). It is important to note, our ability to detect a recent bottleneck is dependent on the level of genetic diversity pre-and postdecline as ancient reductions in genetic diversity may mask recent declines (e.g., Dussex, Rawlence, & Robertson, 2015). While the strength of the decline appears to be greater within Hawaiian gallinule than Hawaiian coot, coincident with the reduction in census size, these species exhibit similar life history characteristics and generation times (7 and 6 years, respectively; BirdLife International 2016b,c).…”
Section: Population Demographymentioning
confidence: 99%